Towards innovation resilience through urban networks of co-invention: A case study of cities in China - Ma, Haitao; Xu, Xuanfang; Li, Xiaozhen; Liu, Jingyu (Frontiers in Earth Science, 2022)
The intensified competition for innovation among countries and the various risks that come with it have made innovation resilience a central concern of the international community in recent years. The concepts of resilience and innovation are inextricably intertwined, however, both theoretical discussions and case studies on innovation resilience are in the “embryonic” stage. This paper attempts to integrate the system and nodes of network resilience, the potential and connectivity of city resilience, and the hierarchy and assortativity of urban network resilience to construct a theoretical analysis framework of inter-city innovation network resilience and conduct a case study on the resilience of patent cooperation network among 338 prefecture-level cities in China during 2017-2019. The results show that the systemic resilience of Chinese urban innovation networks exhibits relatively low hierarchical and yearly decreasing disassortative characteristics, and the node resilience shows a spatial pattern of high in the southeast and low in the northwest, as well as higher innovation resilience in cities with higher administrative levels. The results provide insight into the overall systemic and internal structural characteristics of innovation resilience in Chinese urban networks, and also expand the application of resilience concepts in the field of innovation research from the perspective of urban networks.